Architectural Practice in the Digital Age: Balancing Adoption and Adaptation (EAAE Annual Conference Proceedings, 2023)
The digital age presents both challenges and opportunities for the architectural profession. Architects must navigate the integration of new technologies, such as artificial intelligence (AI) and digital design tools while adapting to the evolving scope of their practice. This paper investigates the balance between adoption and adaptation in architectural practice, exploring strategies for architects to effectively engage with the digital landscape while maintaining the integrity of their profession. The outcomes of fully embracing new technologies and methodologies are contrasted with the approach of modifying existing practices to accommodate digital advancements, considering the implications for the architectural profession.